Development of Contextual Teaching and Learning-Based E-LKPD Mathematics with Malay Context to Improve Students' Mathematical Skills in Cube and Block Material - Syutaridho Syutaridho; Harisman Nizar; Dyah Rahmawati; Muktir Rotul Rodoh; Risky Amelia; Salsabilla Fitri; Salsa Nur Asma (Department of Mathematics Education Program IPI Garut, 2025)
Tuntutan kurikulum yang mengharuskan siswa memiliki kemampuan kritis dan bernalar yang baik dalam menyelesaikan masalah matematik, mengharuskan guru memiliki kemampuan mendesain pembelajaran, dalam penelitian ini memadukan teknologi dalam lembar kerja peserta didik menjadikan E-LKPD sebagai Solusi yang dapat digunakan dalam proses pembelajaran. Penelitian ini bertujuan menghasilkan E-LKPD materi kubus dan balok menggunakan Pendekatan CTL dengan Konteks Melayu yang valid dan praktis serta memiliki efek potensial terhadap kemampuan matematis siswa. Hasil penelitian memberikan gambaran bahwa ada capaian 61,1 % atau ada 22 siswa kemampuan matematis siswa kategori sangat baik, 19,4 % atau ada 7 siswa kategori Baik, 11,1% atau ada 4 siswa kategori cukup, dan 8,3% atau ada 3 siswa kategori kurang. Sehingga efektivitas E-LKPD berbasis pendekatan Contextual Teaching and Learning (CTL) yang dikembangkan dalam meningkatkan kemampuan pemahaman matematis siswa dapat disimpulkan memberikan efek potensial yang baik terhadap kemampuan pemahaman matematis siswa. Curriculum requirements that require students to have good critical and reasoning skills in solving mathematical problems require teachers to have the ability to design learning. In this study, integrating technology into student worksheets makes E-LKPD a solution that can be used in the learning process. This study aims to produce E-LKPD materials on cubes and blocks using the CTL approach with a valid and practical Malay context that has a potential effect on students' mathematical abilities. The results of the study show that 61,1% or 22 students achieved a very good level of mathematical ability, 19,4% or 7 students achieved a good level, 11,1% or 4 students achieved an adequate level, and 8,3% or 3 students achieved a poor level. Therefore, the effectiveness of E-LKPD based on the Contextual Teaching and Learning (CTL) approach developed to improve students' mathematical comprehension skills can be concluded to have a potentially positive effect on students' mathematical comprehension skills.